2012
DOI: 10.1080/10913211.2012.10721889
|View full text |Cite
|
Sign up to set email alerts
|

Does Cost Efficiency Lead to Better Financial Performance? A Study on Taiwan International Tourist Hotels

Abstract: The purpose of this study is to conduct an investigation into the link between cost efficiency and financial performance as it pertains to the hotel industry. This study employs DEA approach to estimate cost efficiency and uses three traditional financial indicators, such as the ratio of net operating profit before taxes, the ratio of earnings before taxes, and return on assets before taxes, to measure financial performance.Data were generated from 68 hotels in the international tourist hotels in Taiwan from 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…A direct positive association between the efficiency and the FP of Tunisian hotels was found by Aissa and Goaied (2016). However, a contradictory argument was presented by Shieh (2012), in a study that used the financial data of 68 Taiwanese hotels; this study found that FP has an insignificant positive relationship with efficiency. Following the direction of the previous literature (Aissa & Goaied, 2016;Barros, 2005;Charnes et al, 1978;Hwang & Chang, 2003;Neves & Lourenço, 2009;Sigala, 2004;M.-M. Yu & Lee, 2009), and using data envelopment analysis (DEA), this study examines the relationship between managerial efficiency and the FP of corporate hotels in Sri Lanka.…”
Section: Efficiencymentioning
confidence: 95%
“…A direct positive association between the efficiency and the FP of Tunisian hotels was found by Aissa and Goaied (2016). However, a contradictory argument was presented by Shieh (2012), in a study that used the financial data of 68 Taiwanese hotels; this study found that FP has an insignificant positive relationship with efficiency. Following the direction of the previous literature (Aissa & Goaied, 2016;Barros, 2005;Charnes et al, 1978;Hwang & Chang, 2003;Neves & Lourenço, 2009;Sigala, 2004;M.-M. Yu & Lee, 2009), and using data envelopment analysis (DEA), this study examines the relationship between managerial efficiency and the FP of corporate hotels in Sri Lanka.…”
Section: Efficiencymentioning
confidence: 95%
“…Moreover, they found that chain systems, tourist guides, and international transportation can significantly improve the cost efficiency of ITHs in Taiwan. Shieh (2012) employed the DEA approach to measure the cost efficiencies of 68 ITHs in Taiwan from 1997 to 2006, and used Tobit regression to investigate the relationship between cost efficiency and financial performance. The financial indicators of the study are the ratio of net operating profit before taxes, ratio of earnings before taxes, and return on asset before taxes.…”
Section: Hotels' Efficiency In Taiwanmentioning
confidence: 99%
“…A positive impact of efficiency on profitability was confirmed by Aissa and Goaied (2016), Guillén, Rengifo and Ozsoz (2014), Fageda and Voltes-Dorta (2012), Mostafa (2010) or Greene and Segal (2004), among others. On the contrary, Palečková (2015), Shieh (2012), Keramidou et al (2013) or Olson and Zoubi (2011) identified only a small or no relationship between efficiency and profitability. Despite the existence of many studies focusing on the link between efficiency and profitability, little attention has been paid to this relationship in the tourism sector.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Despite the existence of many studies focusing on the link between efficiency and profitability, little attention has been paid to this relationship in the tourism sector. We have found only two studies that examined hotels (Aissa andGoaied, 2016 andShieh, 2012) and one paper dealing with travel agencies (Sellers-Rubio and Nicolau-Gonzálbez, 2009). Aissa and Goaied (2016) examined 27 hotels operating in Tunisia and used the DEA approach to measure efficiency and the ROA indicator for profitability performance.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation